La disciplina en la convivencia escolar en los niños de la escuela de educación básica Doctor Federico González Suárez, de la ciudad de Piñas, provincia de El Oro, periodo lectivo 2014 - 2015. - Cajamarca Pintado, Jéssica Elizabeth (2015)
A school has the responsibility to form the individual not only with knowledge but also based on values, experiences, sharing experience and exploring the world, so in the present investigation was planned as main objective to investigate the methodological strategies as a teaching instrument teachers used to improve discipline and school life in children and thus achieve quality education through discipline to build a peaceful and harmonious school life, for that reason.